THE INFLUENCE OF PROPHETIC LEADERSHIP ON ACADEMIC SUPERVISION IN FACING THE DIGITAL ERA (A SEQUENTIAL EXPLANATORY MIXED METHOD APPROACH) - Hikmah Eva Trisnantari; Zahrotunnisa Siswahyuningsih; Prim Masrokan Mutohar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The head of the madrasah is required to carry out adaptive academic supervision in the transformation of learning in the digital era. This study aims to analyze the influence of prophetic leadership on academic supervision, as well as to explain the implementation of prophetic leadership values in carrying out academic supervision at MTsN 1 Tulungagung. This research uses a Sequential Explanatory Mixed Method approach. The quantitative phase was conducted through a survey of 39 teachers and analyzed using simple linear regression. The qualitative phase was conducted through in-depth interviews with the head of the madrasah, the vice principal of curriculum, and 3 teachers, participatory observation, and a documentation study to provide an in-depth explanation of the quantitative research results. The results of the study indicate that prophetic leadership has a positive and significant effect on academic supervision with a regression coefficient value of 0.729 (t = 6.587; p < 0.001). Qualitative findings reveal that the value of siddiq is realized through transparency and objectivity in supervisory activities; amanah through consistency in guidance; tabligh through dialogical communication and constructive feedback; and fathanah through the ability to analyze teachers' needs and adaptive innovation. The synergy of these four values enables academic supervision to remain oriented towards enhancing teachers' professionalism, even within the context of learning that is continuously undergoing digital transformation. This study confirms that in the context of madrasahs in the digital era, the success of academic supervision is determined not only by supervisory procedures but also by the quality of prophetic leadership of the madrasah principal.